Multi locus sequence typing of clinical Burkholderia pseudomallei isolates from Malaysia. - Revathy Arushothy; Fairuz Amran; Nazirah Samsuddin; Norazah Ahmad; Sheila Nathan (Public Library of Science (PLoS), 2020)
Background Melioidosis is a neglected tropical disease with rising global public health and clinical importance. Melioidosis is endemic in Southeast Asia and Northern Australia and is of increasing concern in Malaysia. Despite a number of reported studies from Malaysia, these reports are limited to certain parts of the country and do not provide a cohesive link between epidemiology of melioidosis cases and the nation-wide distribution of the causative agent Burkholderia pseudomallei. Methodology/principle findings Here we report on the distribution of B. pseudomallei sequence types (STs) in Malaysia and how the STs are related to STs globally. We obtained 84 culture-confirmed B. pseudomallei from confirmed septicaemic melioidosis patients from all over Malaysia. Prior to performing Multi Locus Sequence Typing, the isolates were subjected to antimicrobial susceptibility testing and detection of the YLF/BTFC genes and BimA allele. Up to 90.5% of the isolates were sensitive to all antimicrobials tested while resistance was observed for antimicrobials typically administered during the eradication stage of treatment. YLF gene cluster and bimABp allele variant were detected in all the isolates. The epidemiological distribution patterns of the Malaysian B. pseudomallei isolates were analysed in silico using phylogenetic tools and compared to Southeast Asian and world-wide isolates. Genotyping of the 84 Malaysian B. pseudomallei isolates revealed 29 different STs of which 6 (7.1%) were novel. ST50 was identified as the group founder followed by subgroup founders ST376, ST211 and ST84. A low-level diversity is noted for the B. pseudomallei isolates described in this study while phylogenetic analysis associated the Malaysian STs to Southeast Asian isolates especially isolates from Thailand. Further analysis also showed a strong association that implicates agriculture and domestication activities as high-risk routes of infection. Conclusions/significance In conclusion, MLST analysis of B. pseudomallei clinical isolates from all states in Malaysia revealed low diversity and a close association to Southeast Asian isolates.